WATER SAVING TECHNOLOGIES FOR POLYMER AND IRRIGATION MELIORATION (NATURAL SCIENCES MAGISTRATES) - Akhmedjonov D. G. (European Science Publishing, 2024)
This study highlights the importance of improving furrow irrigation techniques to enhance water conservation, as emphasized by the International Commission on Irrigation and Drainage (ICID). The research focuses on the implementation of subsurface anti-filtration screens made from interpolymer complexes (IPC) to optimize irrigation efficiency. Conducted in the “Omad” farming enterprise of the Urtachirchik district, Tashkent region, the experiments compare furrow irrigation with and without subsurface screens during the 2016 growing season. Key findings reveal a significant reduction in water consumption through irrigation between the rows and increased cotton yields. The application of IPC screens at plow layer depth demonstrated reduced deep infiltration, improved water distribution uniformity, and minimized water runoff. Results indicated that irrigation through inter-row furrows led to 123.0 mm of water savings per season. Additionally, cotton yields increased by 5.9 c/ha, generating an annual economic benefit of $305 per hectare. This research validates the efficiency of scientifically based irrigation practices in conserving water and boosting productivity in cotton farming.
Keywords: Furrow irrigation, water-saving technologies, interpolymer complex (IPC), subsurface anti-filtration screens, cotton farming, water conservation, agricultural productivity, economic efficiency, irrigation efficiency.